Penerapan Personal Protective Equipment Pada Workshop Politeknik Ilmu Pelayaran Makassar - Syahrisal Syahrisal; Paulus Pongkessu; Mahadir Sirman; Heny Pasandang Nari (Politeknik Negeri Ujung Pandang, 2019)
Implementation according to the rules of occupational safety and health is needed in all jobs that are useful to avoid things that are not desirable, such as work accidents. The workforce consists of educated and trained people. One of the educated people referred to is the D-IV and DP-III graduates of the Makassar Shipping Polytechnic, because one of the fillers in the world of work is the Polytechnic graduate. The learning process while in the laboratory must be a serious concern in order to get qualified prospective workers, especially understanding about the application of occupational safety and health (K3) especially the use of personal protective equipment so that there are no direct or indirect obstacles in the work, such as work accidents occur, damage to machinery, cessation of production processes, environmental damage and expenses related to work accidents. The purpose of this research is to find out the availability and analyze the application of personal protective equipment to occupational safety and health in the workshop. This research includes the type of survey research with quantitative methods. This design seeks to determine the PPE facilities available at the Workshop, symbols / cues about occupational safety and health, the conditions of the practice room and what percentage of PPE use by cadets during practice. The data collection method is done by using a questionnaire and documentation used to determine PPE facilities available in the Workshop, symbols / cues about occupational safety and health, the conditions of the practice room and what percentage of the use of PPE cadets during practice. The conclusion is that the personal protective equipment (PPE) facilities in the workshop have been provided by the workshop and can be used by cadets or pasis and safely in accordance with government regulations, and the knowledge, understanding and application of cadets towards PPE have reached an average of 95%